Low Calorie Sweetener (LCS) use and energy balance - Peters, John C. (Physiol Behav, 2016)
For thirty years there has been a debate about whether low calorie sweeteners (LCS) provide a benefit for body weight management. Early studies showed that, when consumed alone in a beverage, appetite and food intake were increased. Some observational longitudinal cohort studies reported an association between LCS usage and increasing BMI, suggesting that LCS may actually promote weight gain. In the ensuing decades numerous additional observational and experimental trials have been conducted with the experimental trials nearly uniformly showing a benefit for LCS, either in weight loss or weight gain prevention. The observational trials have been more inconsistent with two recent meta-analyses indicating either a small positive association between LCS usage and BMI (weighted group mean correlation, p=0.03) or an inverse association with body weight change (−1.35 kg, p=.004). Numerous potential mechanisms have been explored, mostly in animal models, in an attempt to explain this association but none have yet been proven in humans. It is also possible that the association between LCS and BMI increase in the observational studies may be due to reverse causality or residual confounding. Randomized controlled trials are consistent in showing a benefit of LCS which suggests that simple behavioral engagement by individuals attempting to control their weight is a sufficiently strong signal to overcome any potential mechanism that might act to promote energy intake and weight gain. Based on existing evidence, LCS can be a useful tool for people actively engaged in managing their body weight for weight loss and maintenance.